COLLABORATIVE PEMERINTAH DESA DAN MASYARAKAT DALAM PENGELOLAAN DESA WISATA ULU MUSI TROKON DI CAWANG LAMA KABUPATEN REJANG LEBONG - Aditia Arjuansyah; Rosidin; Novliza Eka Patrisia (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
Management of the Ulu Musi Trokon Tourism Village in Cawang Lama. This tourism village utilizes the natural potential of the Musi River, which was previously a traditional stone quarry. This study aims to analyze how collaborative processes involving the village government and community can enhance the sustainability and economic empowerment of the village. Through a qualitative approach using interviews, observations, and documentation, the research findings indicate that despite challenges such as limited skills and understanding, this collaboration successfully encouraged community participation in planning, organizing, and implementing the development of tourism facilities. Additionally, the synergy between the village government and the community plays a crucial role in maintaining the sustainability and upkeep of the village's tourism facilities. This effective collaboration has boosted the local economy and introduced the natural tourism potential of Ulu Musi Trokon Village to tourists, thereby providing long-term benefits for the well-being of the community.